The order of prepositional phrases in the structure of the clause - Schweikert, Walter (Linguistik aktuell, 2005)
For a long time prepositions seemed to enjoy a clandestine status in linguistic research. This has changed with a novel path of inquiry into the inner structure of complex prepositional expressions. In a unique approach to the examination of the outer syntax of prepositions the author uses established and new syntactic and statistical tests to achieve a convincing hierarchy of thematic roles expressed by prepositional phrases. From an antisymmetric point of departure the author presents an overview of possible derivations that result in the observed different word orders of PPs in VO and OV la.